Dinâmica espaço temporal do uso e cobertura no bioma mata atlântica no litoral norte e agreste baiano: quantificação de padrões espaciais no período (2000-2016) - Soares, Silvana Oliveira Wenceslau (2019)
Changes in the landscape by anthropic actions are mainly related to socioeconomic development, so the various land use and land cover can result in several types of impacts on the environment, be they positive or negative. The North Coast and Agreste Baiano have undergone several changes in their spatial structure over time. Therefore, the objective of this study was to understand the dynamics of its use and coverage in the multitemporal series from 2000 to 2016, quantifying its spatial patterns through landscape ecology methods and geoprocessing techniques. The mapping of the use and coverage of the study area in the time series (2000-2016) was made through the Google Earth Engine platform and access to the Mapbiomas collection 2.3, the raster files were reclassified into seven categories: Agropastoris, Forest Formations , Mangrove, Field, Bodies of water, Beaches and dunes and Urban Infrastructure. For the quantification of these classes, the metrics CA, NP, LPI and PLAND were calculated in the Fragstats software (McGarigal ; Marks, 1985). The area metric (CA) indicated a gradual decrease in the area of forest formations by 20%, accompanied by a 29% increase in agropastoral areas and a 263% increase in urban infrastructure expansion during the annual period 2000 to 2016, the metric ( LPI), indicated that the largest fragment of forest formations occupies 22.7% of the total region of study. Understanding the spatial patterns that can affect biodiversity and other ecological processes is important in the landscape, as it may help in future work that is related to the conservation of biodiversity and maintenance of various ecological processes. In this way the results of the quantification of the spatial patterns of the regions of the North Coast and Agreste Baiano in the period of 16 years (2000-2016) represent a support tool for studies aimed at the conservation of environmental resources and assistance in management actions and decision making to this region of study